Dampak Minat dan Motivasi Terhadap Prestasi Belajar: Kajian pada Mahasiswa - Fatchuroji, Acep; Damayanti (Jurnal Biogenerasi, 2024)
The purpose of this study is to determine the influence of interest on the learning achievement of students of the 2020–2023 Economics Education study program, the influence of motivation on learning achievement, and the influence of interest and motivation on learning achievement simultaneously. This research involved 160 Economics Education students. This study collected 62 subjects with determination using the slovin formula. Quantitative methods are used in this study. Multiple linear regression analysis was carried out using the SPSS version 23 tool. According to the results of hypothesis testing, namely the t-test and the F test, partial interest has a positive but insignificant effect on the learning achievement of students of the Economic Education study program batch of 2020–2023; Partial interest also has a positive and significant effect on learning achievement